2021
DOI: 10.1590/1984-3143-ar2020-0228
|View full text |Cite
|
Sign up to set email alerts
|

Using vaginal discharge score (VDS) grading system to evaluate the effect of clinical endometritis on reproductive performance of dairy cows in China

Abstract: Clinical endometritis (CE) is a major cause in affecting the reproductive performance of dairy cows. The objectives of this study were to ascertain the prevalence of CE and to evaluate the effect of CE on reproductive performance in dairy cows using vaginal discharge score (VDS) grading system. 803 dairy cows were examined by vaginoscope with 4-point VDS at 26 ± 3 days in milk (DIM) and classified into six groups: non-endometritis with VDS 0 (control; CON), endometritis with VDS 1 (MEM), non-treated endometrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
5
1
1
Order By: Relevance
“…The overall prevalence of clinical endometritis was 42.77% in different tribal areas of Himachal Pradesh and was higher than overall prevalence (3.4-40%) reported in the world (Gilbert et al 2005). The present prevalence was higher than 33% but lower than 69.8% recorded by Wang et al (2021) and Ribeiro et al (2014), respectively. The disparity in the prevalence of endometritis compared to the above-mentioned reports can be due to differences in the management system under which the cows were maintained.…”
contrasting
confidence: 73%
“…The overall prevalence of clinical endometritis was 42.77% in different tribal areas of Himachal Pradesh and was higher than overall prevalence (3.4-40%) reported in the world (Gilbert et al 2005). The present prevalence was higher than 33% but lower than 69.8% recorded by Wang et al (2021) and Ribeiro et al (2014), respectively. The disparity in the prevalence of endometritis compared to the above-mentioned reports can be due to differences in the management system under which the cows were maintained.…”
contrasting
confidence: 73%
“…It not only influences the normal fertility of cows but also brings about great economic losses to the livestock industry ( 21 ). At present, antibiotics are the main treatment for most cow endometritis, but their disadvantages, such as the increase of bacterial resistance and drug residues, outweigh their advantages ( 22 , 23 ). It has been previously shown that IFN-τ has an anti-inflammatory property ( 16 , 17 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endometritis reduces reproductive performance in dairy cows and different management programs have been implemented to improve and control the endometritis such as intramuscular injection of prostaglandin F 2α (PGF 2α ) and intrauterine infusion of antibiotics (Dubuc et al 2021;LeBlanc et al 2002b;Wang et al 2021). Response to the treatment of clinical endometritis and the subsequent improvement of the reproductive performance varies among reports.…”
Section: Introductionmentioning
confidence: 99%